Visualizing ferromagnetic domains in magnetic topological insulators - Wenbo Wang; Fang Yang; Chunlei Gao; Jinfeng Jia; G. D. Gu; Weida Wu (APL Materials, 2015)
We report a systematic study of ferromagnetic domains in both single-crystal and thin-film specimens of magnetic topological insulators Cr doped (Bi0.1Sb0.9)2Te3 using magnetic force microscopy (MFM). The temperature and field dependences of MFM and in situ resistance data are consistent with previous bulk transport and magnetic characterization. Bubble-like ferromagnetic domains were observed in both single crystals and thin films. Significantly, smaller domain size (∼500 nm) with narrower domain wall (∼150 − 300 nm) was observed in thin films of magnetic topological insulators, likely due to vertical confinement effect. These results suggest that thin films are more promising for visualization of chiral edge states.